Low-profile dipole antenna with parasitic patches - Ta, Son Xuat; Chien, Ngoc Dao; Kedze, Kam Eucharist; Park, Ikmo (2017 IEEE 6th Asia-Pacific Conference on Antennas and Propagation, APCAP 2017 - Proceeding, 2018)
This paper presents a low-profile broadband antenna, which is composed of four parasitic patches placed between a printed-dipole radiator and a perfect electric conductor ground plane. The radiator and parasitic patches are realized on thin substrates. Owing to the presence of parasitic patches, the antenna performance improves significantly. The antenna design with the overall dimensions of 120 mm × 120 mm × 16.3 mm (0.64λo × 0.64λo × 0.087λo at 1.6 GHz) has a -10 dB impedance bandwidth of 1.465-1.740 GHz, a broadside gain of 8.5-8.8 dBi.
Keywords: Antenna design; Antenna performance; Broad-band antenna; Impedance bandwidths; Low-profile dipole antennas; Parasitic patch; Perfect electric conductor; Thin substrate